A microchip electrophoresis-based fluorescence signal amplification strategy for highly sensitive detection of biomolecules. Issue 2 (14th December 2016) - Qin, Yingfeng; Zhang, Liangliang; Li, Shuting; Zhao, Jingjin; Huang, Yong; Zhao, Shulin; Liu, Yi-Ming
Abstract : A microchip electrophoresis-based fluorescence signal amplification strategy was developed for highly sensitive detection of biomolecules. Abstract : We have developed a microchip electrophoresis (MCE)-based fluorescence signal amplification strategy as a universal MCE method for the detection of trace biomolecules. This strategy exhibits high sensitivity and specificity for target molecules, and has been applied for the detection of interferon-gamma (IFN-γ) in human plasma with satisfactory results.